Penatalaksanaan Holistik Dermatitis Kontak Iritan Pada Pekerja Bangunan - Muhammad Ega Alfarizi; Azelia Nusadewiarti (Medula, 2020)
Irritant contact dermatitis is a skin disorder that can be found in about 85-98% of all skin diseases caused by work in Indonesia. Symptoms of burning, stinging and pain relief after exposure to cement and wood dust which are irritating. Pharmacologic treatment and preventive measures using personal protective equipment (PPE) are important in the management of occupational dermatitis. Study analysis in this case report identified risk factors and clinical problems in patients by implementing a holistic and comprehensive family doctor approach and its management with holistic and comprehensive, patient centered, family focused, and community oriented by conducting health promotion intervention methods, applying healthy behaviors with precaution adoption process model and treatment of irritant contact dermatitis based on evidence based medicine. Primary data obtained through history taking, physical examination and home visits to complete family data, psychosocial and environmental data. Assessment is based on a holistic diagnosis from the beginning, process, and end of study quantitatively and qualitatively. Patients have aspects of internal risk lack of knowledge about irritan contact dermatitis, curative treatment patterns, behavior that does not use personal protective equipment when working. The external risk aspect for patients is the lack of knowledge and family support in treatment. Furthermore, holistic management of patients and families is carried out through health promotion intervention methods in the form of information about irritan contact dermatitis such as educating the precipitating factors and emphasizing the importance of using personal protective equipment (PPE) when working. In the evaluation it was found that the patient’s complaints were reduced, sufficient knowledge of the disease, changes in patient behavior, and application of personal protective equipment (PPE) at work. Holistic management can improve knowledge, attitudes, and behavior in patients.